INTRAEPITHELIAL LYMPHOCYTES IN THE DUODENAL MUCOSA OF MEAT QUAILS RECEIVING DIETS CONTAINING OR NOT CONTAINING PROBIOTIC AND DIFFERENT LEVELS OF CRUDE PROTEIN - Zardo, Andressa; Otutumi, Luciana Kazue; Mezalira, Taniara Suelen; Ferreira, Fabiane Antiquera; Cestari, Igor Eduardo Dias; Amaral, Patrícia Franco Gonçalves Previato do; Silveira, Alysson Polzonoff (Arquivos de Ciências Veterinárias e Zoologia da UNIPAR, 2015)
The aim of this study is to evaluate the effect of probiotic supplementation associated to different levels of crude protein (CP) on the count of intraepithelial lymphocytes (IELs) in the duodenum of meat quails. A total of 2304 quails were distributed in a completely randomized design in a 2 x 4 factorial scheme (with and without probiotic and four levels of CP - 15, 20, 25 and 30%), with two replicates per treatment in two experimental periods, in a total of 32 experimental units. At seven days old, two quails from each experimental unit were euthanized to harvest the duodenum segment. Semi-serial 7-?m histological sections were obtained, which were subsequently stained with hematoxylin-eosin to perform the IEL count. For the calculation, first 2500 epithelial cells were counted from the mucosa of each animal, and then the IELs present between these cells were counted, with the results expressed in amounts of IELs/100 epithelial cells. No differences were found in the IEL count among the treatments. Under the experimental conditions, it can be concluded that the use of probiotic associated to different levels of CP supplementation does not alter the IEL count in the duodenum of meat quails.